APLIKASI POLYMERASE CHAIN REACTION-RIBOSOMAL INTERGENIC SPACER ANALYSIS (PCR-RISA) UNTUK MENENTUKAN KERAGAMAN MIKROBA TANAH PADA HABITAT TANAMAN PISANG DENGAN DAN TANPA GEJALA LAYU FUSARIUM - I Made Sudarma; Dewa Ngurah Suprapta; I Made Sudana; I Gede Rai Maya Temaja (Bumi Lestari Journal of Environment, 2012)
A major problem in the soil microbiology is 99% soil microbes could not be grown in artificial media; therefore, to describe the true diversity of microbes in the soil must use a molecular approach. The approach was polymerase chain reaction-ribosomal intergenic spacer analysis (PCR-RISA). This method can be used for determining soil microbial DNA profile (the number of DNA bands). The soil samples were collected from three regencies in Bali,  i.e. Karangasem, Klungkung and Jembrana which are the main banana growing area in Bali. Soil sampling was done in two sites in each regency representing the banana habitat with and without Fusarium wilt symptom, by collecting 100 grams of soil surrounding the banana plant at the depth of 20 cm. The result of PCR-RISA showed that DNA profile of the soil microbes in the soil of banana habitat without Fusarium wilt symptom (HN) more than of the soil banana habitat with Fusarium wilt symptom (HF). DNA profiles at HN there were three, each of the indicated 450 bp, 250 bp and <100 bp, whereas in HF were two bands of DNA, each indicated as 250 bp and <100 bp. Based on the number of DNA bands proved that the soil microbial community in the HN is higher than in HF.